2021
DOI: 10.4049/jimmunol.2100168
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Generated from Human Hematopoietic Stem and Progenitor Cells through TLR4 Signaling Promotes Emergency Granulopoiesis by Regulating Transcription Factor Expression

Abstract: Emergency granulopoiesis, also known as demand-adapted granulopoiesis, is defined as the response of an organism to systemic bacterial infections, and it results in neutrophil mobilization from reservoir pools and increased myelopoiesis in the bone marrow. Indirect and direct initiating mechanisms of emergency granulopoiesis have been hypothesized. However, the detailed mechanism of hyperactive myelopoiesis in the bone marrow, which leads to granulocyte left shift, remains unknown. In this study, we report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…( 29 ) and Schurch et al ( 86 ) demonstrated that HSPCs and MSC produced IL-6 in response to inflammatory signals that stimulate HSC mobilization and myeloid differentiation in neutropenia or to promote clearance of the infection. More recently, it has been shown that TLR4 signaling-derived IL-6 promotes emergency granulopoiesis by phosphorylating C/EBP-α/β ( 87 ).…”
Section: Interleukinsmentioning
confidence: 99%
“…( 29 ) and Schurch et al ( 86 ) demonstrated that HSPCs and MSC produced IL-6 in response to inflammatory signals that stimulate HSC mobilization and myeloid differentiation in neutropenia or to promote clearance of the infection. More recently, it has been shown that TLR4 signaling-derived IL-6 promotes emergency granulopoiesis by phosphorylating C/EBP-α/β ( 87 ).…”
Section: Interleukinsmentioning
confidence: 99%
“…Higher expression of TNFSF10 in the liver was also observed in chickens (Abdalla et al, 2004), mandarin fish (Gao et al, 2008) and Japanese pufferfish (Biswas et al, 2015). As the liver maintains the optimal liver mass/body mass ratio by maintaining a 'dynamic equilibrium' between proliferation and apoptosis in hepatocytes (Fausto et al, 2006), the TNF-induced signalling pathway initiates factor κB (NF-κB) (Barut et al, 2020;Sasaki et al, 2021). The head kidney and spleen are secondary lymphoid organs in teleost fish, and play important roles in fish immunology.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide and Poly I:C, two kinds of pathogen‐associated molecular patterns, elicit an acute inflammatory response and promote the release of multiple cytokines in leucocytes and macrophages by activating TLR‐related signalling pathways, such as mitogen‐activated protein kinase (MAPK) pathways and nuclear factor κB (NF‐κB) (Barut et al., 2020; Sasaki et al., 2021). The head kidney and spleen are secondary lymphoid organs in teleost fish, and play important roles in fish immunology.…”
Section: Discussionmentioning
confidence: 99%
“…C/EBPb and C/EBPa were also found to play key roles in the differentiation of human CD34+ cells towards the myeloid lineage in response to LPS in vitro. In this case, however, LPS activated a TLR4-MD2-MyD88 pathway that resulted in the expression of IL-6, which in turn, induced C/EBPa and C/EBPb phosphorylation, finally promoting monocytic-macrophage differentiation (57). Direct TLR4 triggering of HSCs also plays an important role in the maintenance of HSC fitness.…”
Section: Direct Tlr Ligation Promotes Trained Immunity In the Hspc Poolmentioning
confidence: 95%